2022
DOI: 10.1177/00207640221135849
|View full text |Cite
|
Sign up to set email alerts
|

Religiousness and psychotic experiences among young adult college students in the United States

Abstract: Background: Religiousness and psychotic experiences have been related, though findings have been mixed, with little attention paid to specific religious affiliations and religious importance. Methods: We analyzed data from the Healthy Minds Study (2020–2021), which was an online survey administered at 140 college campuses across the United States. We used multivariable logistic regression to examine the associations between religiousness (affiliation and importance) and 12-month psychotic experiences, adjustin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Moreover, a meta‐analysis showed a protective effect of religion on suicide mortality (Wu et al, 2015). In view of the evidence demonstrating the association of religion with other mental health outcomes (Braam & Koenig, 2019; Oh et al, 2022), our findings could have differed had we utilized different research settings.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, a meta‐analysis showed a protective effect of religion on suicide mortality (Wu et al, 2015). In view of the evidence demonstrating the association of religion with other mental health outcomes (Braam & Koenig, 2019; Oh et al, 2022), our findings could have differed had we utilized different research settings.…”
Section: Discussionmentioning
confidence: 92%
“…Evidence-based research has found that the prevalence of PEs youth ranges from 8% to 24% [5,6]. Recent studies have reported that the prevalence of PEs in college students is 16% in the U.S. [7], 24% in the United Kingdom, 13% in China, and 20% in Japan [6]. PEs are common in adolescence, often co-occur with mental disorders [8][9][10][11], and may increase the risk of depression, anxiety, and substance abuse during adolescence [12][13][14], and of psychosis later in life [15].…”
Section: Introductionmentioning
confidence: 99%